A descriptive review of next-generation insecticide-treated bed nets for malaria control - Böhmert, Antonia L.; Logan, Rhiannon A. E.; Portwood, Natalie M.; Hartke, Juliane; Ingham, Victoria A. (Frontiers in Malaria, 2024)
To date, insecticide-treated bed nets are the most effective tool in preventing malaria-related morbidity and mortality. All distributed bed nets contain pyrethroid insecticides; however, widespread resistance to this class in the malaria vectors, Anopheles spp., has led to the development of dual active ingredient bed nets, termed ‘next-generation bed nets’. These nets combine pyrethroids with a second chemistry, aimed at countering pyrethroid resistance. The World Health Organization (WHO) recently issued recommendations for three classes of next-generation bed nets. In this review, we report on key indicators across Africa for each net type. The results underscore a substantial variation in key indicators across Africa when comparing next-generation bed nets to traditional pyrethroid-only nets. Nevertheless, dual active ingredient bed nets generally outperform pyrethroid-only nets in a various settings. The results show that new nets are a formidable tool in malaria control, with superior performance compared to traditional pyrethroid-only nets. The variability in outcomes across Africa underscores the need for a region-specific approach, fostering a targeted and adaptive strategy for the deployment of these next-generation interventions.